Strategy beyond the hockey stick : people, probabilities, and big moves to beat the odds - Bradley, Chris; Hirt, Martin ;Smit, Sven (Hoboken, New Jersey : John Wiley & Son, Inc., 2018)
Beat the odds with a bold strategy We've all seen hockey stick business plans before. A future where results sail confidently upward, but with a dip coinciding with next year's budget. CEOs usually rely on their experience and business smarts to figure out which of those hockey sticks are real, and which are fake. But all too often getting to a "yes," competing for resources, and striving to claim credit, cloud the hard decisions. Another strategy framework? No thanks, we already have plenty of those, and they don't fix the real problem: the social dynamics in your strategy room. Mining the data from thousands of large companies, McKinsey Partners Chris Bradley, Martin Hirt and Sven Smit open the windows of that room, and bring an "outside view." They found three discrete groups of companies: the bottom quintile with massive economic losses; the long, flat, middle 60 percent with practically no economic profit; and the top 20 percent to whom all the value accrues. Some companies do achieve real hockey stick performance: but just 1-in-12 jump from the middle tier to the top over a ten year period. This does not happen by magic--there is an empirically-backed science to improve your odds of success by capitalizing on your endowment, riding the right trends, and most importantly, making a few big moves. To make these big moves happen, you're going to have to break through inertia, gamesmanship and risk aversion. You're going to have to mitigate human biases and manage group dynamics. Eight practical shifts can help you do this, and unlock bigger, bolder, better strategies. This is not another by-the-book approach to strategy. It's not another trudge through frameworks or small-scale case studies promising a secret formula for success. It's an irreverent, fact-driven, and humorous take on the real world of strategic decision making.
Introduction: Welcome to the strategy room -- Games in the strategy room and why people play them -- Opening the windows of your strategy room -- Hockey stick dreams, hairy back realities -- What are the odds? -- How to find the real hockey stick -- The writing is on the wall -- Making the right (big) moves -- Eight shifts to unlock strategy -- Epilogue: New life in the strategy room.
Includes index.
Keywords: STRATEGIC PLANNING